Early Formula Supplementation Differs by Maternal Body Mass Index but Does Not Explain Breastfeeding Outcomes in Mothers Who Intend to Exclusively Breastfeed - Shannon C Conrey; Laurie Nommsen-Rivers; Allison R Burrell; Mary A Staat; Ardythe L Morrow (Current Developments in Nutrition)
Background: Early formula supplementation (EFS, formula on birthdate or day after) is associated with maternal obesity and reduced breastfeeding, but the effect of prenatal breastfeeding intention on these relationships is understudied. Objectives: We evaluated how EFS affected breastfeeding outcomes after controlling for obesity, sociodemographic and health factors. Methods: Multivariable regression modeling, stratified by prenatal breastfeeding intention. Conclusions: Our findings suggest that EFS may be less disruptive to breastfeeding in mothers with strong intention to meet breastfeeding recommendations, regardless of maternal BMI.